PENGEMBANGAN MEDIA PEMBELAJARAN PEMBELAHAN SEL DENGAN MENGGUNAKAN MACROMEDIA FLASH UNTUK KELAS XII SMA - Lestari, Rena (Universitas Pasir Pengaraian, 2014)
This research was conducted to developing Biology media-learning by employing macromedia flash in studying cell division for X grade high school students based on the result of validation by the expert team and the students responses. This research used a developing research based on Dick and Carey model which were modified.Data collection was be conducted by providing questionnaires. In analyzing the data by descriptive analysis. The results of this research shows that: (1) the test by Biology experts in light of evaluating content appropriateness is on very good criteria (84%); (2) the test by media-learning experts is on very good criteria (88%); (3) the individual test is on very good criteria (83%); (4) the group test is on very good criteria (81%); (5) the field test is on very good criteria (85%).